การคาดคะเนลักษณะของใบมีดจากรอยที่ปรากฏบนผ้าเนื่องจากการแทง - ณีรนุช ใจคนอง (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Tears appearing on the fabric due to stabbing with bladed weapons are material evidence in criminal cases able to be associated to investigation for tools used in commitment of the offense, including sequences of circumstances of deaths. This research aims to study and compare sizes and nature of the tears of cotton from stabbing with different bladed weapons. In this experiment, four types of knives including paring knives, kitchen knives, pocket knives, and folding knives were used to stab through the cotton fabric and caused tears on the fabric, controlling direction of stabbing and movement of volunteers who are targeted so that the pricks that made are similar to the real situations. Then the tears on the fabric caused by such stabbing were recorded with a digital camera before analyzing to determine correlation between the forms of the pricks and the nature of the knives. The results showed that the pricks caused by each kind of bladed weapon had different specific characteristics. Analysis of the sizes and forms of the pricks, accompanying with examination on tearing of the fibers, enables to estimate type of bladed weapon more accurately.